An Analysis on Distracters of Multiple Choices on Student Worksheet Used By SMPN 2 Sumberrejo, Bojonegoro - Sri Liswoyowati; Jarum Jarum (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2014)
An Analysis on Distracters of Multiple Choices on Student Worksheet Used By SMPN 2 Sumberrejo, Bojonegoro